Pulmonary Adenocarcinomas of Low Malignant Potential: Proposed Criteria to Expand the Spectrum Beyond Adenocarcinoma In Situ and Minimally Invasive Adenocarcinoma. (April 2021) - Yambayev, Ilyas; Sullivan, Travis B.; Suzuki, Kei; Zhao, Qing; Higgins, Sara E.; Yilmaz, Osman H.; Litle, Virginia R.; Moreira, Paulo; Servais, Elliot L.; Stock, Cameron T.; Quadri, Syed M.; Williamson, Christina; et al.
Abstract : Lung cancer screening has improved mortality among high-risk smokers but has coincidentally detected a fraction of nonprogressive adenocarcinoma historically classified as bronchoalveolar carcinoma (BAC). In the National Lung Screening Trial (NLST) the majority of BAC—comprising 29% of computed tomography–detected stage I lung adenocarcinoma—were considered overdiagnosis after extended follow-up comparison with the control arm. In the current classification, adenocarcinoma in situ and minimally invasive adenocarcinoma have replaced BAC but together comprise only ∼5% of stage I lung adenocarcinoma. Lepidic and subsets of papillary and acinar adenocarcinoma also infrequently recur. We, therefore, propose criteria for low malignant potential (LMP) adenocarcinoma among nonmucinous adenocarcinoma measuring ⩽3 cm in total, exhibiting ≥15% lepidic growth, and lacking nonpredominant high-grade patterns (≥10% cribriform, ≥5% micropapillary, ≥5% solid), >1 mitosis per 2 mm 2, angiolymphatic or visceral pleural invasion, spread through air spaces or necrosis. We tested these criteria in a multi-institutional cohort of 328 invasive stage I (eighth edition) and in situ adenocarcinomas and observed 16% LMP and 7% adenocarcinoma in situ/minimally invasive adenocarcinoma which together (23%) approximated the frequency of overdiagnosed stage I BAC in the NLST. The LMP group had 100% disease-specific survival. The proposed LMP criteria, incorporating multiple histologic parameters, may be a clinically useful "low-grade" prognostic group. Validation of these criteria in additional retrospective cohorts and prospective screen-detected cohorts should be considered. Abstract : Supplemental Digital Content is available in the text.